Relevant factors affecting nurse staffing: a qualitative study from the perspective of nursing managers - Gege Li; Gege Li; Waner Wang; Jiangfeng Pu; Zhanghao Xie; Yixuan Xu; Tiemei Shen; Huigen Huang; Huigen Huang (Frontiers Media S.A., 2024)
ObjectiveTo understand the current situation of nursing manpower allocation, explore the factors affecting nurse staffing, improve nurse staffing level, and provide reference for better formulation of nursing human resources staffing standards.MethodsA descriptive research method was used to conduct semi-structured interviews with 14 nursing managers. The data were analyzed and refined by content analysis. The sample size was subject to content saturation.ResultsNine themes and twenty sub-themes of influencing factors for nursing staffing were identified across four levels: hospital level, department level, patient level, and nurse level.ConclusionHospital and department managers need to comprehensively consider the factors of affecting nurse staffing. Adopting multidimensional optimization measures, improving relevant systems, optimizing nurse structure, and establishing flexible and mobile nurse database to cope with public emergencies, so as to effectively improve nurse staffing and nursing service quality.